A Cognitive Functional Therapy+ Pathway Versus an Interdisciplinary Pain Management Pathway for Patients With Severe Chronic Low Back Pain (CONFeTTI Trial): Protocol for a Pragmatic Randomized Controlled Trial. Issue 9 (17th May 2021) - Vaegter, Henrik Bjarke; Johansen, Jannick Vaaben; Sopina, Liza; Smith, Anne; Kent, Peter; Fuglsang, Kira Søndberg; Pedersen, Jesper Fredslund; Schutze, Rob; O'Sullivan, Peter; Handberg, Gitte; Fatoye, Francis; Ussing, Kasper; et al.
Abstract: Objective: Chronic low back pain (cLBP) is the leading cause of disability. Interdisciplinary pain management is recommended for patients with severe/high-impact cLBP. Such programs are expensive, not easily accessible, and have limited effect; therefore, new cost-effective strategies are warranted. Cognitive functional therapy (CFT) has shown promising results but has not been compared with an interdisciplinary pain management approach. The primary aim of this randomized controlled trial is to investigate if a pathway starting with CFT including psychologist support (CFT+) with the option of additional usual care (if needed) is superior in improving disability and more cost-effective at 12 months compared with an interdisciplinary pain management pathway (usual care). Methods: This pragmatic, 2-arm, parallel-group randomized controlled trial will randomly allocate patients (n = 176) aged 18 to 75 years referred to an interdisciplinary pain center due to severe cLBP to 1 of 2 groups (1:1 ratio). Participants randomized to CFT+ will participate in a 3-month functional rehabilitation pathway with the option of additional usual care (if needed), and participants randomized to the interdisciplinary pain management pathway will participate in an individualized program of longer duration designed to best suit the individual's situation, needs, and resources. The primary outcome is the proportion of participants with an 8-point improvement in the Oswestry Disability Index score at 12 months. Exploratory outcomes are change in Oswestry Disability Index scores over time and an economic analysis of quality-adjusted life years using the 3-level version of the EuroQol EQ-5D. Impact: The study evaluates the cost-effectiveness of CFT+ with the option of additional usual care (if needed) for individuals with severe cLBP. Findings can potentially improve future care pathways and reduce cost for the health care system.